Psoriatic Arthritis in Males and Females: Differences and Similarities - Ennio Lubrano; Silvia Scriffignano; Mauro Fatica; Paola Triggianese; Paola Conigliaro; Fabio Massimo Perrotta; Maria Sole Chimenti (Rheumatology and Therapy, 2023)
Abstract Objective To assess any differences and similarities in psoriatic arthritis (PsA) between sexes. Any possible differences of psoriasis and its potential impact on disease burden between sexes with PsA were also evaluated. Methods Cross-sectional analysis of two longitudinal PsA cohorts. The impact of psoriasis on the PtGA was evaluated. Patients were stratified in four groups based on BSA. The median PtGA was then compared between the four groups. Moreover, a multivariate linear regression analysis was performed in order to evaluate associations between PtGA and skin involvement, split by sexes. Results We enrolled 141 males and 131 females: PtGA, PtPnV, tender, swollen joint count, DAPSA, HAQ-DI, PsAID-12 were statistically significant higher in females (p ≤ 0.05). PASS “yes” was deemed more in males than in females and BSA was higher in males. MDA was present more in males than females. When the patients were stratified on BSA, median PtGA was not different between males and females with BSA = 0. Instead, in females with BSA > 0, a higher PtGA was observed compared to males with BSA > 0. There was not a statistically significant association between skin involvement and PtGA at linear regression analysis, even if a trend seems to be present in female. Conclusions Psoriasis is more present in males, but it seems to be related to a worse impact in females. In particular, a possible role of psoriasis as an influencing factor the PtGA was found. Moreover, female PsA patients tended to have more disease activity, worse function, and higher disease burden.